Understanding the Implications of a Punitive Approach to Homelessness: A Local Case Study. Issue 2 (4th June 2018) - Wilking, Jennifer; Roll, Susan; Philhour, David; Hansen, Peter; Nevarez, Holly
Abstract : Cities large and small are increasingly using public safety policies to address local concerns about homelessness. In 2013, Chico, California, followed suit by passing several ordinances, most notably, a "sit‐lie" ordinance that prohibits individuals from sitting or lying in commercial districts and other public spaces. Broadly, this article explores the implications of this punitive approach to homelessness. Specifically, relying primarily upon arrest data extending over six and a half years, we explore how enforcement of the sit‐lie ordinance affected arrest rates of homeless individuals, as well as the geographic location of those arrests. Our expectations are supported—arrests of homeless individuals increased significantly in the "post sit‐lie" period, and the location of arrests clearly shifted away from the downtown area. Finally, given economic motivations of the ordinances, we estimate the costs to city law enforcement of policing the homeless population and find that costs are nearly twice as large as police department estimates.